2014
DOI: 10.1007/s40257-014-0096-2
|View full text |Cite
|
Sign up to set email alerts
|

Topical Therapy for Toenail Onychomycosis: An Evidence-Based Review

Abstract: Topical treatment with amorolfine, ciclopirox, tavaborole, or efinaconazole is appropriate for cases of mild to moderate toenail onychomycosis due to dermatophyte or mixed dermatophyte/Candida infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 36 publications
1
43
0
1
Order By: Relevance
“…PRO analyses of topical treatments are limited, likely in part because numerous studies have demonstrated the clinical superiority of oral medications [36,37]. Additionally, until recently, ciclopirox was the only topical drug approved for onychomycosis treatment in the US [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PRO analyses of topical treatments are limited, likely in part because numerous studies have demonstrated the clinical superiority of oral medications [36,37]. Additionally, until recently, ciclopirox was the only topical drug approved for onychomycosis treatment in the US [36].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, until recently, ciclopirox was the only topical drug approved for onychomycosis treatment in the US [36]. With the approval of efinaconazole and tavaborole in 2014, more QOL studies are warranted given the high cost and nonsuperiority of these medications to oral antifungals [37].…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the clinical efficacy of different treatments is often difficult. Oral treatments are commonly believed to be more efficacious than topical ones, but the standards of evaluation vary among clinical studies, making comparison even more complex [1]. …”
Section: Introductionmentioning
confidence: 99%
“…This nail solution is a combination of propylene glycol (66.4%), urea (20%), and lactic acid (10%), which likely act in combination to produce keratolytic, softening, and antimycotic effects. A randomized double-blind controlled trial reported mycological cure rates with K101 solution that were similar to those reported for ciclopirox and amorolfine lacquers [3]. Patients also reported improvement of clinical symptoms, such as thickening, discoloration, and brittleness of nails [9].…”
Section: Introductionmentioning
confidence: 87%
“…Topical antifungal treatments may be preferred for patients with mild disease or those who are immunocompromised or using multiple medications. However, the efficacy of topical antifungals ranges from 29 to 90% for mycological cure and from 1 to 18% for complete cure [3]. …”
Section: Introductionmentioning
confidence: 99%